Factors influencing tourists readiness to travel during pandemic / Wan Shahrul Aziah Wan Mahamad and Ramli Saad - Wan Mahamad, Wan Shahrul Aziah; Saad, Ramli (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2022)
Some of the countries in this world have been affected by an unprecedented event which is the COVID-19 pandemic. Regional quarantine, lockdown, travel ban, and border closure policies have been issued by most countries to break the chain of the spread of this virus. These restrictions are considered to be most effective in containing the spread between people but indirectly it is strongly affecting the tourism sector (Gossling et al., 2020; Wen et al., 2020). Even though vaccination programs have been implemented in various countries, there is still uncertainty on the effectiveness of the vaccines and also when the pandemic will end (Esterman, 2020), and this may influence tourist readiness to travel during this pandemic.